Strategi Pengendalian Inventory dengan Metode Pendekatan PDCA Pada Phase out Product Sebagai Upaya Mengurangi Deadstock di PT XYZ - RM Temmy Arif Hidayat; Syafira Nur Aulia; Tito Adhy; Akmal Nazarudin; Yudi Prasetyo (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study aims to apply the PDCA (Plan, Do, Check, Act) method as a systematic strategy in inventory control for phase-out products to reduce deadstock at PT XYZ. The background of the study shows a significant increase in the amount of scrapping in the last three years due to the accumulation of uncontrolled deadstock. The research uses a qualitative descriptive approach with data collection techniques through observation, interviews, and historical company data. Through the PDCA stages, it was found that the main causes of deadstock stemmed from the inconsistency of phase-out control methods, manual monitoring processes by the PIC, and uncertainty in customer demand. The implementation of solutions in the form of standardizing control methods, digitizing inventory systems, and implementing an early warning system yielded significant results. The evaluation results showed that the improvement strategy was able to reduce the potential for deadstock by up to 80.7% in the sample product model. Thus, the PDCA method proved to be effective as a continuous improvement approach in inventory control during the product phase-out. This research is recommended to be applied more widely in inventory management in companies-.